CD44-Mediated Poor Prognosis in Glioma Is Associated With M2-Polarization of Tumor-Associated Macrophages and Immunosuppression - Xiao, Yong; Yang, Kun; Wang, Zhen; Zhao, Mengjie; Deng, Yanxiang; Ji, Wei; Zou, Yuanjie; Qian, Chunfa; Liu, Yong; Xiao, Hong; Liu, Hongyi (Frontiers in Surgery, 2022)
Background: Glioma is the most common primary brain tumor with poor prognosis. Key genes negatively related to prognosis may provide therapy targets to cure glioma. To clarify the role of CD44 in glioma, we explored its function at bulk-transcriptome, spatial and single-cell transcriptome level. Methods: In total, expression profiles with survival data of whole-grade glioma from The Cancer Genome Atlas (TCGA) and the Chinese Glioma Genome Atlas (CGGA), RNA-seq data with anatomic information of glioblastoma (GBM) from the Ivy Glioblastoma Atlas Project, RNA sequencing data from recurrent GBM receiving adjuvant anti-PD-1 immunotherapy accessed through GSE121810 and single-cell RNA sequencing data of GBM under accession GSE103224 were enrolled in this study. CD44-specific findings were further analyzed by R language. Results: CD44 is positively correlated with WHO grade of malignancy and is negatively related to prognosis in glioma. Meanwhile, CD44 predominantly expresses in GBM mesenchymal subtype, and Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis reveal that CD44 positively co-expressed genes are closely related to glioma immunity. Moreover, CD44+ cells mainly distribute in perinecrotic region with high expression of immune factors. At single-cell resolution, only malignant tumor cells, tumor-associated macrophages (TAMs), T cells express CD44 in GBM. CD44+ malignant tumor cells are in mesenchymal-1-like (MES1-like) cellular state, and CD44+ TAMs are in M2 phenotype. CD44+ T cells have high expression of both PD-1 and PD-L1. CD44 and its directly interacted inhibitory immunomodulators are up-regulated in non-responder recurrent GBM patients treated with PD-1 blockade therapy. Conclusion: Our work demonstrates that CD44, a new M2 TAMs biomarker, is involved in immune suppressor and promote glioma progression in glioma microenvironment. These results expand our understanding of CD44-specific clinical and immune features in glioma.